Use of somatic hybridisation to transfer resistance to late blight and Potato Virus Y (PVY) into cultivated potato - Thieme, Ramona; Darsow, Ulrich; Rakosy-Tican, Lenuta; Kang, Zhensheng; Gavrilenko, Tatjana; Antonova, Olga; Heimbach, Udo; Thieme, Thomas (Plant Breeding and Seed Science, 2004)
Protoplast fusion was used to produce more than 500 symmetric interspecific somatic hybrids between wild Solanum species, which belong to the series Pinnatisecta, Etuberosa and S. tuberosum L. cultivars or potato breeding clones. The used genebank accessions of S. cardiophyllum and S. tarnii were resistant to Phytophthora infestans, while the accessions of S. cardiophyllum, S. tarnii, as well as of S. etuberosum, were also highly resistant to PVY (strains: PVYO, PVYN, PVYNTN, PVYC, PVYN Wilga). In most fusion combinations vigorous and genetically stable hybrid material has been selected. A number of interspecific somatic hybrids were fertile and could be backcrossed with cultivated potato. The use of detached leaf and tuber tests and mechanical inoculation, grafting and virus transmission by vectors, revealed that several somatic hybrids and backcross (BC) clones were resistant to foliage and tuber blight, as well as to PVY.